The Effect of Conflict in Inflammatory Peace and Social-Development in Northeast, Nigeria - Dahiru Idriss, Ibrahim (‘Abqari Journal, 2022)
The paper aims to examine on Boko Haram conflict and its effect on social development and peaceful atmosphere of Muslim community. Historically antecedent toward under development as a result of conflict. The paper went further to explain the modus-operandi of the group that encompasses killings of innocent people, bombing places of worship, raping and kidnapping in the name of religion to achieve their barbaric goals. The negative effect of the terrorists group (Boko Haram) activities on the social development in Yobe State of Nigeria has become so devastating that even some of the financial institutions and other commercial ventures shut-down in many areas of the state especially the state capital (Damaturu), thereby causing relocation of many people to various safe places within and even outside the region. It is based on the aforementioned that this paper seeks to explore the extent to which Boko Haram insurgency has affected the peace and social development in Yobe State of Nigeria. The paper explains the concepts of conflict, peace and social development; the research used focus groups discussion to generate information and gain knowledge on the extent of effect of the conflict on social development. The paper concluded that Boko Haram constitute a serious problem to the development of various sectors in the State. It was recommended among others that the institution of Zakat and endowment be revive and all stakeholders should put hands on deck towards the realization of high level of peace and social security by strategizing different ways of fighting the menace of Boko Haram in the region.